Benefits of stereotactic ablative radiotherapy combined with incomplete transcatheter arterial chemoembolization in hepatocellular carcinoma - Paik, Eun Kyung (Radiat Oncol, 2016)
BACKGROUND: This study aimed to evaluate the effect of stereotactic ablative radiotherapy (SABR) after incomplete transcatheter arterial chemoembolization (TACE) in hepatocellular carcinoma (HCC) patients. METHODS: The study enrolled 178 HCC patients initially treated with TACE between 2006 and 2011. Patients were included if they had Barcelona Clinic Liver Cancer stage 0 or A, ≤3 nodules with a total sum of longest diameter ≤10 cm, Child-Turcotte-Pugh score of ≤7, no major vessel invasion, and no extra-hepatic metastases. RESULTS: Twenty-four patients achieved a complete response to TACE (group 1). Among those with incomplete response, 47 patients received other curative treatments (group 2), 37 received SABR (group 3), and 70 received non-curative treatments (group 4). The 2–year overall survival (OS) rates for groups 1, 2, 3, and 4 were 88 %, 81 %, 73 %, and 54 %, respectively. The corresponding 5-year OS rates were 50 %, 58 %, 53 %, and 28 %, respectively. CONCLUSIONS: Patients treated with SABR after incomplete TACE had similar survival outcomes to those achieving complete response to TACE or receiving curative treatments. However, patients receiving non-curative treatments had significantly lower survival rates than the other groups. Therefore, if SABR was indicated at the initial diagnosis, it might be recommended after TACE failure.